Impact of the COVID‐19 pandemic on the psychological health of individuals with mental health conditions: A mixed methods study. Issue 4 (24th September 2021) - Miller, Alexia E.; Mehak, Adrienne; Trolio, Vittoria; Racine, Sarah E.
Abstract: Objectives: This study explored how the coronavirus disease 2019 (COVID‐19) pandemic has affected individuals with mental health conditions. Methods: Participants were 477 adults (82% female) who reported a past‐year mental health condition. They completed an online survey that included an open‐ended question. Mixed methods analysis was conducted. Results: While all mental health conditions were moderately impacted by the COVID‐19 pandemic, self‐reported impact on anxiety disorder and obsessive‐compulsive disorder symptoms was greater than for all other mental health symptoms. Thematic analysis revealed five themes: (1) the contribution of the pandemic to worsening mental health; (2) life interruptions due to the pandemic; (3) increased loneliness/isolation; (4) upsides of the pandemic; and (5) normalization of the anxieties previously experienced by those with mental health conditions. Conclusion: Individuals with pre‐existing mental health conditions reported a worsening of symptoms during the COVID‐19 pandemic. Governments and organizations must focus on supporting and increasing access to treatment for this population.